STN EN 27435: 2001 (02 1183), Nastavovacie skrutky s drážkou a čapíkom. - Lutzová, Irena; Lutz, František; Sekerešová, Drahomíra (Slovenský ústav technickej normalizácie, 2001)
Táto národná norma je identická s EN 27435: 1992